Increased atherosclerotic plaque in AOC3 knock-out in ApoE−/− mice and characterization of AOC3 in atherosclerotic human coronary arteries - Filip, Anna; Taleb, Soraya; Bascetin, Rümeyza; Jahangiri, Mohammad; Bardin, Matthieu; Lerognon, Cindy; Fève, Bruno; Lacolley, Patrick; Jalkanen, Sirpa; Mercier, Nathalie (Frontiers in Cardiovascular Medicine, 2022)
Amine oxidase copper containing 3 (AOC3), displays adhesion between leukocytes and endothelial cells and enzymatic functions. Given its controversial role in atherogenesis, we proposed to investigate the involvement of AOC3 in the formation of atherosclerotic plaques in ApoE-/-AOC3-/- mice and human coronary arteries. Lesions, contractile markers and AOC3 were studied in aortic tissues from 15 and 25 week-old mice and different stage of human coronary atherosclerotic arteries by immunohistochemistry (IHC) and/or western blot. Human VSMCs treated or not with LJP1586, an AOC3 inhibitor, were used to measure differentiation markers by qPCR. AOC3 co-localization with specific cell markers were studied by confocal microscopy in mice and human samples. Results: At 15-week-old, the absence of AOC3 was associated with an increased lesion size, -SMA and CD3 staining’s in the plaque independently of a cholesterol modification. At 25-week-old, advanced plaques were larger with equivalent staining for -SMA while CD3 increased in the media from ApoE-/-AOC3-/- mice. At both ages, macrophage content of the lesion was not modified. Contractile markers decreased whereas MCP-1 appeared augmented only in 15-week-old ApoE-/-AOC3. AOC3 is mainly expressed by mouse and human VSMC slightly expressed by endothelium but not by macrophages. AOC3 knock-out increased atherosclerotic plaques at an early stage related to a VSMC dedifferentiation associated with higher T cells recruitment in plaques explained by the MCP-1 augmentation. This suggests that AOC3 may have an important role in atherosclerosis independent of its canonical inflammatory effect. The dual role of AOC3 impacts therapeutic strategies using pharmacological regulators of SSAO activity.